Competitividade na cadeia de valor da avicultura de corte - Fiuza Sobrinho, Reinaldo (2010)
The aim of this study was to analyze the competitiveness of a cooperative from Paraná participant in the chain of poultry, using the value chain analysis. From the methodological point of view, the research is documentary, explanatory and takes a case study nature. The research is explanatory because it aims to identify factors that determine or contribute to the occurrence of phenomena. In relation to the documentary procedure, the investigation has focused on competitiveness issues, strategic cost management and on understanding of the role of companies in promoting regional development. This is a case study involving the poultry production activity of a cooperative that is present almost all over the West of Paraná, specifically Lar Agribusiness Cooperative, with its head office in Medianeira. This choice is justified by the similarity of its poultry production chain to the other cooperatives in the region, which adopt modern technologies in the production of chicken, slaughter and distribution of final products. To develop this study it was adopted the methodology of building the value chain inserted into the theoretical framework of strategic cost management, and the research has used as base the formation of the value of boneless chicken breast sold to the customer Super Poultry in Europe. It was found that the main critical links in the value chain involve the relationship between the area of grain and the poultry steering committee, and the relationship between the company studied and the farmer engaged in chicken rearing. The research has identified the occurrence of short-term contracts in the value chain, specifically when it involves the active matrix chick. The research has also revealed that the company needs to improve its competitiveness through reduced cost of live chicken ready for slaughter. The company has proved to be competitive in the share of the cost of live chicken that is the producer s responsibility, but needs to act on the variable costs of the share of the cost of live chicken rearing. It was observed as well that the cost of corn, soybean meal, fertile egg and the quantity produced are the main components of the value chain that alter the average cost of the chicken breast studied. Finally, the study has identified opportunities for improvement in cost of inputs and raw materials, through better corporate management of the procurement process, establishment of long-term partnerships with suppliers and competitors, as well as the creation of strategic stocks of raw materials. Accordingly, the hypothesis of this study was confirmed by identifying that some critical factors for competitiveness in costs were not known by the poultry industry managers at the time of their decisions on the planning and marketing of chicken meat.